Equity, equality and equivalence : a contribution in search for conceptual definitions and a comparative methodology - Moreno Herrera, Lázaro (Revista Española de Educación Comparada, 2007)
Issues of equity, equality and equivalence are currently a cross-national concern; policy making in education takes importance notice of social and political demands largely associated to different notions of social justice. Conceptualization and empirical studies remains, nevertheless, a controversial endeavour due to the variety of aspects underpinning the discourses on these categories. Cross-national comparative studies however, need a well-defined conceptual and methodological framework. In this article it is argued that the current debate on conceptual and methodological issues could benefit from the contributions of social and cultural reproduction theory and a pluralistic methodological approach to comparative studies. The article contains no answers but perspectives on the various questions and challenges; the purpose of this article is to make an initial contribution to the ongoing debate on conceptualization of these categories and to highlight some of the challenges of cross-national comparative studies in this subject. Equidad, igualdad y equivalencia en los sistemas educativos es en la actualidad un tema de interés para la comunidad académica en diferentes contextos. El diseño de políticas educativas en diferentes marcos nacionalespresta atención a exigencias políticas y sociales estrechamente vinculadas adiferentes conceptos de justicia social. La conceptualización y la realización de estudios empíricos se hacen controversiales debido a la diversidad deaspectos en los cuales se sustenta el discurso en relación con estas tres categorías. La investigación comparativa necesita sin embargo de un claro marco conceptual y metodológico para poder operar. Este artículo argumenta queel actual debate de aspectos conceptuales y metodológicos puede beneficiarse considerablemente de contribuciones como la teoría de reproducción culturaly de un enfoque metodológico más plural a los estudios comparativos. El artículo no pretende dar respuesta a las problemáticas que aborda; su propósito fundamental es contribuir al debate actual en estudios de comparativos de equidad en educación y resaltar algunos de los desafíos más importantes para estudios comparativos sobre esta temática